PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA SMK NEGERI 1 KENDIT - Septian, Bayu Aditya; Arief, Muhammad Yahya; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of this study was to analyze the effect of work motivation and work environment variables on teacher performance through work discipline as an intervening variable at SMK Negeri 1 Kendit. By using the Structural equation model of Partial Least Square (PLS). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, namely work motivation has a significant effect on work discipline, work environment has a significant effect on work discipline, work motivation has a significant effect on teacher performance, work environment has a significant effect on teacher performance, work discipline has a significant effect on teacher performance , Work motivation has a negative but not significant effect on teacher performance through work discipline, and the work environment has a negative but not significant effect on teacher performance through work discipline.